Pelatihan Guiding untuk Pemuda ASIDEWI & Pokdarwis di Desa Wisata Kampung Patin Koto Masjid Kampar - Syaifullah; Herlinawati; Syahdan (Indra Institute Research & Publication, 2023)
Kampung Patin or Koto Masjid Kampar village offers a wide variety of tourism products, such as culinary, nature and souvenirs. The last three years this village has been visited by many tourists from neighboring provinces, such as West Sumatra, North Sumatra and Jambi. In 2021, this village was awarded the ADWI (Indonesian Tourism Village Award) by the minister of Tourism. In addition, in the same year it also won the second National Champion award as a tourism village in the field of souvenirs. The results of the initial survey of researchers through the chairman of ASIDEWI (Association of Tourism Villages) Koto Masjid, after a lengthy discussion related to the progress of the village, especially in tourism, collaboration with related parties is urgently needed, especially to improve the quality of tourism actors there. Furthermore, the chairman of ASIDEWI said that;